PENGARUH FAKTOR-FAKTOR OSEANOGRAFI TERHADAP HASIL TANGKAPAN SERO DI PULAU KARAMPUANG KAB. MAMUJU SULAWESI BARAT - Arwin Rawin; Muhammad Ardiansyah (Jurnal Perikanan Unram, 2024)
Sero is a type of fishing gear whose operation is carried out around coastal waters, is permanent, and has the role of trapping fish that have territorial areas around the coast or fish that migrate towards the coast. The oceanographic conditions of a body of water can be used to indicate fishing areas for certain types of fish. This research aims to determine the influence of oceanographic factors (temperature, salinity, currents, and tides) on sero catches on Karampuang Island, Mamuju Regency, West Sulawesi. The research was carried out in June-July 2023 on Karampuang Island, District. Mamuju, West Sulawesi. This method uses a field survey method, namely measuring temperature, salinity, tides, and currents. The results of this study indicate that the influence of oceanographic parameters on the total sero catches yield together with the independent variables (X) does not have a significant impact on the sero catches yield (Y). Individually (partially), the variable with a negative value, the temperature on serocatch but not substantial.